2017
DOI: 10.1016/j.ijrobp.2017.06.1974
|View full text |Cite
|
Sign up to set email alerts
|

Management of Local-Regional Failure in Children With High-Risk Neuroblastoma: A Single Institution Experience

Abstract: all patient and tumor factors, adults were associated with less chance of receiving RT (pZ0.002) but not surgery (pZ0.084). The median and 5 year OS of adults continued to be significantly worse than those of pediatrics (p < 0.0001) which could be partially secondary to a lower chance of having RT in adults. Conclusion: Adult patients with PMS had inferior survival as compared to pediatric patients even following propensity matching of all patient and tumor factors. Adults had less odds of receiving RT which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…NB exhibits diverse clinical behavior, from spontaneous remission [ 5 ] to a widespread metastatic disease with poor outcomes and event-free survival rates below 50% [ 2 , 6 , 7 ]. Despite intensive treatment regimens, the prognosis for patients with high-risk relapsed or treatment-refractory NB remains poor and novel treatment strategies are urgently needed [ 8 , 9 ]. The pre-treatment risk stratification for this cancer relies on the International Neuroblastoma Risk Group (INRG) classification system, including age at diagnosis, histologic category, grade of tumor differentiation, tumor cell ploidy, 11q aberration and status of the oncogene MycN [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…NB exhibits diverse clinical behavior, from spontaneous remission [ 5 ] to a widespread metastatic disease with poor outcomes and event-free survival rates below 50% [ 2 , 6 , 7 ]. Despite intensive treatment regimens, the prognosis for patients with high-risk relapsed or treatment-refractory NB remains poor and novel treatment strategies are urgently needed [ 8 , 9 ]. The pre-treatment risk stratification for this cancer relies on the International Neuroblastoma Risk Group (INRG) classification system, including age at diagnosis, histologic category, grade of tumor differentiation, tumor cell ploidy, 11q aberration and status of the oncogene MycN [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data presented by Modak and colleagues and Manole and colleagues indicate that patients with isolated local recurrence can be treated successfully with surgical tumor resection and/or radiation therapy at sites of active disease [ 6 , 7 ]. These authors further recommend using chemotherapy regimens with demonstrated activity in children with recurrent neuroblastoma, rather than experimental therapy for localized relapses.…”
Section: Introductionmentioning
confidence: 99%